Incidence Rates of Surgery After Knee MRI: Association According to Referring Physician Type and Patient's Age and Sex. Issue 11 (10th November 2021) - Naqvi, Syed R.; Beavis, R. Cole; Mondal, Prosanta; Bryce, Rhonda; Leswick, David A.
Background: The utility of magnetic resonance imaging (MRI) in the primary care setting is uncertain, with a perception that there is less likelihood for surgery after MRI ordered by general practitioners (GPs) when compared with orthopaedic surgeons and sports medicine physicians. Additionally, the influence of patient age and sex on subsequent surgical intervention is currently unknown. Purpose/Hypothesis: The purpose of this study was to compare surgical incidence after MRI referrals by orthopaedic surgeons, GPs, and sports medicine physicians, including a subset analysis for GP patients based on type of approval given by the radiologist. The authors also wanted to explore the association of age and sex on subsequent surgical intervention. They hypothesized that surgical incidence after MRI ordered by orthopaedic surgeons and sports medicine physicians would be higher than after MRI ordered by GPs. Study Design: Cohort study; Level of evidence, 3. Methods: Knee MRI referrals by the 3 physician cohorts during May to December 2017 were assessed. For GP patients, the types of approval or recommendation from a radiologist were categorized. Subsequent surgical intervention status was then compared among referral groups up to 2 years after MRI. Associations of age and sex with surgical occurrence were also assessed. Chi-square test, analysis of variance, and univariate/multivariable logistic regression were used for statistical analysis. Results: Overall, 407 referrals were evaluated (GP, n = 173; orthopaedic, n = 176; sports medicine, n = 58). Surgical incidence was not significantly higher for orthopaedic and sports medicine than GP referrals at 3 months (10%, 3%, and 6%, respectively; P = .23), 6 months (20%, 17%, and 15%; P = .49), and 2 years (30%, 35%, and 24%; P = .25). Surgical incidence for GP patients was higher after discussion with a radiologist or when evaluating specific pathology on prior imaging versus less defined reasons (30.4% vs 15.7%, respectively; P = .03). Surgical incidence was lower for older patients (11% vs 31% for >60 years vs all other age groups combined; P = .002), and women were less likely to undergo surgery than men (22% vs 35%, respectively; P = .008). Conclusion: Surgical incidence after MRI was likely appropriately lower for older patients. Lower incidence for female patients is of uncertain cause and warrants further study.